Variations of HIV and STI prevalences within communities neighbouring new goldmines in Tanzania: importance for intervention design. Issue 4 (5th August 2003) - Clift, S; Anemona, A; Watson-Jones, D; Kanga, Z; Ndeki, L; Changalucha, J; Gavyole, A; Ross, D A
Abstract : Objectives: To measure the prevalence of HIV and other STIs in communities neighbouring new large scale gold mines in northern Tanzania in order to inform the design of a targeted HIV/STI intervention programme. Methods: Cross sectional surveys were conducted in adults aged 16–54 years from different sectors of communities neighbouring two newly opened, large scale gold mines near Lake Victoria. Mine workers, men, women, and female food and recreational facility workers (FRFW) from the community were randomly selected for interview and HIV and STI testing. Results: 207 male Tanzanian mine workers, 206 FRFW, 202 other male and 205 female community members were enrolled. Overall, 42% of FRFW were HIV positive, compared to 6% of male mine workers, and 16% and 18% of other community men and women respectively. HIV prevalence in FRFW was significantly associated with alcohol consumption (adjusted odds ratio (aOR) = 2.5, 95% confidence interval (CI) 1.1 to 5.5), past or present syphilis (TPPA+) (aOR = 2.7, 95% CI 1.4 to 5.1) and single status (aOR = 3.8, 95% CI 1.2 to 11.9). Among FRFW, 24% had active syphilis (RPR+, TPPA+), 9% Chlamydia trachomatis, and 4% Neisseria gonorrhoeae . Overall, 50% of FRFW and 50% of community men never used condoms during sex, and 55% mineworkers, 61% male, and 20% female community members reported receiving/giving payment for sex during the previous year. Conclusions: There is a high prevalence of HIV and other STIs in communities around new goldmines in Tanzania, especially in FRFW. HIV and STI prevalence in the mining workforce is still relatively low, but high risk sexual behaviour is reported by all adult subgroups surveyed in this study. Programmes focusing on HIV/STI prevention, with targeted interventions for high risk women such as FRFW, will be extremely important in such high transmission communities where there is substantial recent in-migration of men and women seeking work. Such programmes have recently been initiated by a private/public/NGO partnership.